STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK TUNAGRAHITA - Fauzul Andim; A.Saiful Aziz (Universitas Wahid Hasyim Semarang, 2021)
AbstractEducation is the right of all citizens regardless of origin, caste or physical condition of a person, including children with disabilities. As mandated in the Constitution Number 20 of 2003 concerning the National Education System in article 5 paragraphs 1 and 2 it is stated that